Chromogenomic changes after the use of methyl parathion on Ocimum Americanum L. in Eastern Zone of Nepal - Mishra, KK (BIBECHANA, 2014)
Fungicide like methyl Parathion was able to control the fusarial disease of Ocimum americanum L. but it caused Chromogenomic changes in the first progeny of the host plant. The parental colour was red, which became to green in the ratio 5-95%. Therefore, the use of the fungicide not only control the disease caused by the Fusarium oxysporum but also affects the genomes responsible for the colour. The investigation was from 1/11/2012 to 02/12/2013. DOI: http://dx.doi.org/10.3126/bibechana.v11i0.10391 BIBECHANA 11(1) (2014) 128-130